Теплообмен: теория и практика: учебник - Карнаух В. В. Виктория Викторовна; Бирюков А. Б. Алексей Борисович; Гинкул С. И. Станислав Иванович; Ржесик К. А. Константин Адольфович; Гнитиев П. А. Павел Александрович (Москва, Инфра-Инженерия, 2021)
Авт. указаны на обороте тит. л.